Meta-analysis in systematic reviews of complementary and integrative medicine trials. Issue 3 (December 2016) - Cramer, Holger; Chung, Vincent C.H.
Abstract: In evidence-based medicine, meta-analyses are often considered to provide an exceptionally high level of evidence. Beyond other systematic review formats, meta-analyses allow for statistically pooling results of original research. This approach allows us to increase statistical power, improve precision, investigate heterogeneity, and settle controversies across different clinical trials. However, meta-analysis requires rigour in methodology, in order to avoid "mixing apples and oranges". Study design, participants, interventions, comparators, and outcomes need to be clearly defined, and statistical methods need to be applied precisely. For researchers in specialized fields such as integrative medicine, additional considerations on the unique features of therapies need to be applied. This article describes practical and academic insights into preparing a meta-analysis for publication.